Fear of the COVID-19 and health-promoting lifestyle: the mediating role of corona anxiety - Zahra Baji; Ghodratollah Shakerinejad; Farzaneh Jarvandi; Masoumeh Tehrani (Payesh, 2023)
Objective(s): The present study was conducted aiming to assess the effect of fear caused by COVID-19 on health-promoting lifestyle through the mediation role of anxiety. Methods: This was a cross-sectional study on a sample of employees of government organizations in Ahvaz, Iran in 2021. The required data were collected using a multi-part questionnaire including demographic information, health-promoting lifestyle assessment questionnaire, fear of the corona virus questionnaire, and the anxiety scale for the corona virus. Data were analyzed using path analysis and bootstrap test was used to check the mediating role of variables. Results: In total 384 employees were entered into the study. The mean age of participants was 40.74 ± 6.07 years ranging from 24 to 60. The results showed that there was a positive and significant correlation between the fear of COVID-19 and Covid-19 anxiety (P<0.01). There was a negative and significant correlation between health-promoting lifestyle and both fear and anxiety caused by Corona (P<0.01). Based on the findings the fear caused by Corona and the health-promoting lifestyle had a statistically significant relationship directly and through the anxiety of the Corona disease (P<0.001). Conclusion: The findings suggest that Corona anxiety mediates the relationship between fear of corona and health-promoting lifestyle. In general, with the increase in the fear of corona, the anxiety of corona disease increases and as a result, the health-promoting lifestyle decreases.